Moving - Amos, Janine (Milwaukee, WI : Gareth Stevens Pub., 2002)
Uses letters, stories, and informational text to help children cope with moving to a new home.
Includes bibliographical references (p. [32]).
Keywords: Moving, Household -- Juvenile literature; Moving, Household -- Psychological aspects -- Juvenile literature; Moving, Household -- Social aspects -- Juvenile literature; Moving, Household